Effect of temperature and chemical additives on the short-term ageing of polymer modified bitumen for WMA. (15th December 2018) - Ragni, Davide; Ferrotti, Gilda; Lu, Xiaohu; Canestrari, Francesco
Abstract: Nowadays warm mix asphalt (WMA) is recognized as a very competitive alternative to hot mix asphalt (HMA). This technology allows to obtain an excellent and environmentally-friendly material for road construction. This paper focuses on the effect of a reduced short-term ageing temperature on the binder behaviour and on the effect of WMA chemical additives on the performance of short-term aged binders. Three asphalt binders (one polymer modified bitumen combined with two WMA chemical additives) were aged through the rolling thin film oven test (RTFOT) at different temperatures (120, 130 and 163 °C). Conventional, rheological and chemical tests were used for characterising the binders. Lower ageing temperatures provided reduced oxidation, implying lower oxidative hardening but also reduced permanent deformation resistance. A general reduction of ageing effects is observed in the WMA binders, with both positive (moderate deceleration of the ageing process) and negative (more noticeable reductions in the permanent deformation resistance) outcomes. The microscopic analysis showed that the chemical additive likely alters the structural interactions of bitumen and polymer. A comparison between WMA binders short-term aged in laboratory and in field, indicates that the RTFOT performed at reduced temperature could properly simulate the field ageing when WMA production temperatures are considered. Graphical abstract: Highlights: Chemical additives tend to reduce the effect of short-term ageing on binder performance. Chemical additive type and ageing temperature affect the binder recoverable behaviour. The structural interactions of bitumen and polymer are altered by the chemical additives. Short-term ageing at reduced temperature properly simulates field ageing of warm mix asphalts.